Recent advances in biomarkers and therapeutic interventions for hepatic drug safety - false dawn or new horizon? - Clarke, Joanna I.; Dear, James W.; Antoine, Daniel J. (Expert opinion on drug safety, 2016)
Introduction: Drug-induced liver injury (DILI) represents a serious medical challenge and a potentially fatal adverse event. Currently, DILI is a diagnosis of exclusion, and whilst the electronic evaluation of serious drug-induced hepatotoxicity (eDISH) have revolutionised the early assessment of DILI, this model is dependent upon clinical chemistry parameters that lack sensitivity and specificity. DILI management usually consists of initial withdrawal of the suspected drug and, in the case of acetaminophen, administration of specific therapy. Areas covered: We summarise recent advances and knowledge gaps in the development and qualification of novel DILI biomarkers and therapeutic interventions. Expert opinion: Promising biomarkers have been identified that provide increased hepatic specificity (miR-122), mechanistic insight (Keratin-18), and prognostic information (HMGB1, KIM-1, CSF-1). Pharmacogenomics holds potential to preselect susceptible populations and tailor drug therapy. Biomarkers can uncover new mechanisms of drug-induced pathophysiology which, for HMGB1 and CSF-1, have led to promising mechanism-based therapeutic interventions. However, these biomarkers have not been formally qualified and are not in routine clinical use. With the development of inventive clinical trials and by maximising DILI data registries, these novel biomarkers could add substantial value to the current armoury, change the management of DILI in the near future and improve patient safety.